The Influence Of Consumer Behavior And Product Quality On Product Purchase Decisions In Maximart Yanglim Medan - halim, Cheviria; Valesia tjuang; Seriana; Sulyyani; Kelvin; Mela Novita Rizki (Outline Publisher, 2024)
This research analyzes the influence of consumer behavior and product quality on purchasing decisions at Maximart Yanglim Medan. Maximart Yanglim is a retail company that provides daily necessities products, especially food and other necessities. Product quality is an important factor in influencing consumer purchasing decisions. This study identifies the stages of consumer purchasing decisions, starting from recognizing needs, searching for information, evaluating alternatives, to purchasing decisions and post-purchase behavior. Apart from that, factors such as other people's attitudes and situational factors also influence purchasing decisions.